(Mal)Adaptive Psychological Functioning of Students Utilizing University Counseling Services - Biasi, Valeria; Cerutti, Rita; Mallia, Luca; Menozzi, Francesca; Patrizi, Nazarena; Violani, Cristiano (Frontiers in Psychology, 2017)
Background: University students confront psychological difficulties that can negatively influence their academic performance. The present study aimed to assess several areas of adaptive and maladaptive psychological functioning among university students who request counseling services. Method: One hundred eighty-four young female students seeking professional psychological help (Counseling seekers) and 185 young female students who have never asked for psychological help (Non-counseling seekers) were asked to complete the Adult Self-Report (ASR) to evaluate both their internalizing and externalizing problems through DSM-oriented scales as well as their adaptive functioning. Results: ANOVA results indicated worse psychological functioning for the students who sought counseling. They reported lower score in ASR Adaptive Functioning Scales (i.e. friends, jobs, family, education), and higher scores in DSM-oriented scales (i.e. Depressive, Anxiety, Somatic, Avoidant Personality, Attention Deficit/Hyperactivity symptoms) than the students who never asked psychological help. Furthermore, discriminant analysis successfully discriminated between the two groups of students on the basis of the ASR's adaptive and DSM-oriented scales. Conclusions: The study findings could be useful to guide university counseling services in their screening activities as well as useful for clinical practice.